A new species of Melampyrum (Orobanchaceae) from Southern Korea - Kim, Ki-Joong; Yun, Seok-Min (Phytotaxa, 2012)
A new species, Melampyrum koreanum K.-J. Kim & S.-M. Yun, is described and illustrated. The new species is similar to M. roseum Maxim. in general habit, but the new species has a corolla tube and style up to 3 cm long. The new species occurs on one of the islands of the southern Korean peninsula.